Electroreduction of Oxygen in Alkaline Solution on Iron Phthalocyanine Modified Carbide-Derived Carbons - Zagal-Moya, J; Zagal-Moya, J (Elsevier Ltd, 2019)
Carbide-derived carbons (CDC) are porous carbon materials with tunable pore structure, very high specific surface area and of great potential for electrochemical applications. In this work CDC-supported transition metal macrocyclic electrocatalysts are prepared using two different type of CDC materials and iron phthalocyanine (FePc). Herein, we report the superior electrocatalytic properties of FePc/CDC catalysts fabricated via simple pyrolysis approach. The morphology, composition and structural features of these CDC-based non-noble metal catalysts are evaluated using scanning and transmission electron microscopies, X-ray photoelectron spectroscopy, N 2 physisorption and X-ray diffraction analysis. The electrochemical oxygen reduction reaction (ORR) behavior of FePc/CDC catalysts is evaluated employing the rotating disk electrode (RDE) method. FePc modified CDC materials demonstrate a superior ORR electrocatalytic activity in alkaline conditions, showing onset potential of −0.05 V (vs. SCE) close to that of commercial Pt/C. Thus, the RDE results show great potential of these non-Pt catalysts as cathode materials in metal-air batteries and alkaline membrane fuel cells. © 2019 Elsevier Ltd